What Are We Doing when We Are Doing Philosophy of Education? - Vokey, Daniel James (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
In this paper I describe a research project designed to address the general question “What are we doing when we are doing philosophy of education?” I also describe how the research results are intended to inform three initiatives: (a) designing philosophy of education courses for Bachelor of Education programs; (b) designing graduate programs in philosophy of education; and (c) maintaining courses and programs in philosophy of education by communicating our relevance to people, academics and otherwise, outside our professional circles. The overall objective of the proposed research is to develop and illustrate a defensible account of the nature and role of philosophy in general and philosophy of education in particular, focusing on the potential role of philosophy of education in promoting consensus on norms and priorities for public education by collaborating in the emergence of a new world view through moral inquiry and discourse.